The Evolution of Exchange Rate Regimes Since 1990 : Evidence From De Facto Policies - Bubula, Andrea (IMF Working Papers; Working Paper ;, 2002)
This paper presents a monthly database on de facto exchange rate regimes that covers all IMF members since 1990. Information from IMF country reports and other sources, including exchange rate data, is utilized to determine de facto exchange rate policies. Countries are categorized based on these policies using the IMF nomenclature adopted in 1999. This approach ensures the forward compatibility of the database. The database is then used to examine whether the "bipolar view" of exchange regimes holds with de facto regimes. It is found that the proportion of countries adopting "intermediate" regimes has indeed been shrinking in favor of greater flexibility or greater fixity, especially for countries more integrated with international markets. Analyses based on Markov chains of regime transitions, however, provide (mixed) evidence against the bipolar view.